The Zia episode in Bangladesh politics - Zafarullah, Habib Mohammad (New Delhi : South Asian, 1996)
Contributed papers.
Includes bibliographical references p. 192-200 and index.
Keywords: Rahman, Ziaur; Bangladesh -- Politics and government -- 1971-